Optimization of Zn2, Cd2, Pb2 and Cu2 determination in the coastal water by using voltammetry - Mohamed, Khairul Nizam; Ramjam, Nur Jannati; Qing, Ng Li; Junairi, Aleef Syamim; Ruzahan, Nur Izzati; Abdul Razak, Abdul Rahman Hashimi; Ghani, Mohamad Azrul (Electrochemical Science Group, 2022)
This study was conducted to optimize the use of Anodic Stripping Voltammetry (ASV) for the determination of Zn2+, Cd2+, Pb2+ and Cu2+ ions concentration in the coastal water. Firstly, different UV irradiation periods were applied to the acidic samples (pH 2), natural seawater (pH 8), and coastal water samples so that the metal ions from the natural organic substances could be completely liberated prior to the voltammetry analysis. Undetected metal ions in the samples that did not go through this UV irradiation indicated the presence of natural organic substances that bind to these metal ions. Hence, the distribution of these organic substances plays a crucial role in the binding of trace metals found in coastal water. The results showed that a 5 minutes UV irradiation period was required for the optimal determination of dissolved Pb2+ and Cu2+ concentrations in the sample, while a 30 minutes period was required for dissolved Zn2+ and Cd2+ determination. The different UV irradiation periods required to free different types of metal ions in the same sample suggested the existence of a natural organic-metal complex with different architectures that have different binding strengths for different types of metal ions. Compared to the other existing methods, the optimised voltammetry analysis developed in this study can provide a reliable and effective alternative in analysing seawater samples, especially due to the relatively low costs and high sensitivity of this method.